Determinants of inequality in Latin America: a panel data analysis of the Gini index and socioeconomic variables (1990–2022) - García Sandoval, Carlos (2025)
This study explores the determinants of inequality in Latin America, using the Gini index as the main measure and evaluating its relationship with various socioeconomic variables between 1990 and 2022. Data from 10 countries in the region are used, including Argentina, Bolivia, Brazil, Colombia, Chile, Ecuador, Mexico, Peru, Paraguay, and Uruguay. The main objective is to analyze how factors such as GDP per capita, the poverty rate, life expectancy at birth, public spending on education, the unemployment rate, and investment in research and development influence inequality.The methodology is based on a panel data model, which captures both the differences between countries and the temporal variations over more than three decades. Fixed and random effects regressions were applied to assess the robustness of the results, in addition to conducting Granger causality tests to explore causal relationships between GDP per capita and inequality.The results show that GDP per capita has a negative and significant relationship with the Gini index, indicating that economic growth contributes to reducing inequality in the region. On the other hand, the poverty rate has a significant positive effect on the Gini index, suggesting that higher poverty levels increase inequality. Other variables, such as investment in research and development, also show some influence on inequality, while public spending on education is not significant in most models.These findings highlight the importance of promoting inclusive economic growth and reducing poverty to decrease inequality in Latin America.